2015
DOI: 10.1007/s00595-015-1273-5
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision totally extraperitoneal inguinal hernia repair as a teaching procedure: one center’s experience of more than 300 procedures

Abstract: SILS-TEP was performed safely, with low morbidity and no recurrence, by the resident surgeons under appropriate guidance by staff surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Dallas et al indicated that older age should not influence the decision to perform laparoscopic inguinal hernia repair in a high‐volume laparoscopic medical center (). In our department, the first SILS procedure for colectomy was performed in May 2009 (), and the indications for SILS have been expanded to include cholecystectomy, appendectomy, gastrectomy (), and hernioplasty (). Because SILS is the standard laparoscopic approach for various procedures in our department, surgeons have developed the specific skills needed for SILS, such as manipulation of laparoscopic coagulation shears, forceps, and flexible laparoscope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dallas et al indicated that older age should not influence the decision to perform laparoscopic inguinal hernia repair in a high‐volume laparoscopic medical center (). In our department, the first SILS procedure for colectomy was performed in May 2009 (), and the indications for SILS have been expanded to include cholecystectomy, appendectomy, gastrectomy (), and hernioplasty (). Because SILS is the standard laparoscopic approach for various procedures in our department, surgeons have developed the specific skills needed for SILS, such as manipulation of laparoscopic coagulation shears, forceps, and flexible laparoscope.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no consensus on the indications for hernia repair in the elderly (). SILS for totally extraperitoneal inguinal hernia repair (SILS‐TEP) has better cosmetic outcomes than conventional laparoscopic inguinal hernia repair (). Although the current literature had frequently reported experienced laparoscopic surgeons performing SILS‐TEP safely, there have been few reports evaluating the feasibility and safety of laparoscopic inguinal hernia repair, including SILS‐TEP, for elderly patients ().…”
Section: Introductionmentioning
confidence: 99%
“…The anterior sheath was opened with an approximately 3‐cm incision, and blunt dissection using a finger or gauze was performed between the muscle and the posterior sheath to create a preperitoneal space. After a Lap‐Protector Mini (Hakko Co., Nagano, Japan) was placed in this space, three 5‐mm trocars (one for a 5‐mm flexible scope and two for surgical devices) were inserted through a single‐port access device (EZ Access; Hakko Co.) (Figures ) . The preperitoneal space was dissected gradually using conventional straight laparoscopic instruments without a dissection balloon.…”
Section: Methodsmentioning
confidence: 99%
“…SILS for totally extraperitoneal inguinal hernia repair (SILS‐TEP) is now implemented as a procedure with better cosmetic outcomes than open and conventional laparoscopic inguinal hernia surgery . We previously published a short report showing that totally extraperitoneal (TEP) repair with bridging heparin therapy might be feasible and safe for patients on antithrombotic therapy .…”
Section: Introductionmentioning
confidence: 99%
“…In terms of less early postoperative pain, faster return to usual activities, and reduced chronic pain, meta-analysis results of randomized comparative trials have found it to be superior to open mesh repair [14]. However, it has a steeper learning curve than open mesh repair because of the level of technical difficulty [510]. In fact, laparoscopic hernia repair requires unique skills and understanding of the unfamiliar anatomy of the inguinal region, and serious complications or hernia recurrence can result if the surgeon is inexperienced [11, 12].…”
Section: Introductionmentioning
confidence: 99%